The major adduct of the antitumor drug cis-diamminedichloroplatinum(II) with DNA bends the duplex by approximately equal to 40 degrees toward the major groove. - Rice, J A (1988)
We used gel electrophoresis methods to show that reaction of DNA with cis-diamminedichloroplatinum(II) results in a substantial (approximately equal to 40 degrees) bend in the double helix at the intrastrand crosslink between the N7 atoms of adjacent guanosine nucleosides, which bond to the platinum(II) complex with loss of two chloride ions. Multimers of a 22-base-pair (bp) oligonucleotide platinated at a single site show strong anomalies in their electrophoretic mobilities as a consequence of coherent addition of in-phase platinum-induced bends. Increase of the sequence repeat of the platinated site to 27 bp yields multimers of nearly normal mobility because the bends are out of phase. The direction of Pt-induced bends relative to adenosine-tract bends was determined from the electrophoretic mobility of multimers in which repeated platination sites are interdigitated at various phasings relative to repeated adenosine tracts. Optimum bending occurs when 1.5 helical turns separate the cis-[Pt(NH3)2[d(pGpG)]](N7,N7) adducts from the center of the adenosine tracts. This phasing produces coherent addition of adenosine tract bends toward the minor groove at their centers and Pt-induced bends toward the major groove, where the platinum is located.